PENINGKATAN KEMAMPUAN PEMAHAMAN SISWA PADA PELAJARAN MATEMATIKA MENGGUNAKAN MODEL SNOWBALL THROWING DI KELAS VIII-6 SMP NEGERI 6 PERCUT SEI TUAN - Robinhot Robinhot (JS (JURNAL SEKOLAH), 2020)
Abstract: Improving Students' Understanding Ability in Mathematics Learning Using the Snowball Throwing Model in Class VIII-6 of SMP Negeri 6 Percut Sei Tuan. This study uses a qualitative approach to the type of classroom action research. The subjects of this study were students of class VIII-6 of SMP Negeri 6 Percut Sei Tuan. The data in this study are divided into two types, namely quantitative data and qualitative data. Quantitative data were analyzed by looking for average values and presentations. Whereas qualitative data were analyzed using data analysis techniques consisting of reducing data, presenting data, and drawing conclusions. The results showed that there was an increase in students' understanding abilities in mathematics by using the snowball throwing learning model for students of class VIII-6 of SMP Negeri 6 Percut Sei Tuan 2018/2019. Keywords: Learning Model, Snowbell Throwing, Ability Abstrak: Peningkatan Kemampuan Pemahaman Siswa Pada Pelajaran Matematika Menggunakan Model Snowball Throwing Di Kelas VIII-6 SMP Negeri 6 Percut Sei Tuan. Penelitian ini menggunakan pendekatan kwalitatif dengan jenis penelitian tindakan kelas. Subyek penelitian ini adalah siswa kelas VIII-6 SMP Negeri 6 Percut Sei Tuan. Data dalam penelitian ini terbagi menjadi dua jenis, yaitu data kuantitatif dan data kualitatif. Data kuantitatif dianalisis dengan mencari nilai rata-rata dan presentasenya. Sedangkan data kualitatif dianalisis menggunakan teknik analisis data yang terdiri dari mereduksi data, menyajikan data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa ada peningkatan kemampuan pemahaman siswa pada pelajaran matematika dengan menggunakan model pembelajaran snowball throwing siswa kelas VIII-6 SMP Negeri 6 Percut Sei Tuan Tahun Pembelajaran 2018/2019. Kata kunci: Model Pembelajaran, Snowbell Throwing, Kemampuan